Designing a Crowdsourcing Tool to Analyze Relationships Among Jazz Musicians: The Case of Linked Jazz 52nd Street - Thorsen, Hilary; Pattuelli, M. (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
We discuss the design of Linked Jazz 52nd Street, a crowdsourcing tool using linked data technology to build a social network of jazz musicians through the analysis of their personal and professional relationships.